Analisis harapan UMKM terhadap program e-commerce Dinas Koperasi dan UMKM DIY (Pendekatan studi kualitatif) - Palangan, Citra Yayu' (AITI, 2024)
This study examines the expectations of MSMEs regarding e-commerce programs implemented by Dinas Koperasi dan UMKM DIY. MSME expectations were analyzed using the open-coding method with the QDA Miner Lite software. In total, 59 data on expectations were analyzed and categorized into 14 expectation codes. Subsequently, the researcher selected the top three expectations from the analysis of the codes. The study's findings indicate that the three main expectations of MSMEs are training and mentorship programs, government support for marketing MSME products, and government funding support.